Two new species of Metapocyrtus Heller, 1912 (Coleoptera: Pachyrhynchini) from Mount Natampod, Pantaron Range, Bukidnon, Mindanao, Philippines - Patano, Romeo R. Jr.; Amoroso, Victor B.; Mohagan, Alma B.; Maglangit, Erl Pfian T.; Coritico, Fulgent P.; Yap, Sheryl A. (2022)
Mindanao is home to many unknown weevil species, specifically those remote and unexplored mountain ecosystems. Two new species, Metapocyrtus (Metapocyrtus) mendioi sp. nov. and M. (M.) edmai sp. nov. are described from Mount Natampod, Pantaron Range, San Fernando, Bukidnon, Mindanao, Philippines. -Title page.
Includes bibliographical references.
Keywords: Beetles -- Philippines -- Bukidnon